2020
DOI: 10.3390/chemengineering4040062
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Catalysis—A Simplified Simulation of Catalytic Reactors for CO2 Reduction

Abstract: The realistic numerical simulation of chemical processes, such as those occurring in catalytic reactors, is a complex undertaking, requiring knowledge of chemical thermodynamics, multi-component activated rate equations, coupled flows of material and heat, etc. A standard approach is to make use of a process simulation program package. However for a basic understanding, it may be advantageous to sacrifice some realism and to independently reproduce, in essence, the package computations. Here, we set up and num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…However, on an industrial scale, it is common practice to feed methanol reactors with syngas close to the stoichiometric condition (optimal SN is 2.05 as investigated by Løvik and co-workers) and excess of H 2 (2 < H 2 /CO < 3) with a variable amount of CO 2 (i.e., variable COR) according to the installed syngas generation technology. This means that the most common case in an industrial plant is represented by bio-syngas and petro-syngas feedstocks as reported in the literature case studies ,, and real methanol industrial plants’ data. , However, CO 2 /H 2 mixtures as feedstocks for methanol synthesis are under investigation, and they are becoming more and more appealing for their sustainability and environmental reasons , although carbon capture utilization and sequestration (CCUS) still represents a relevant cost factor in industrial plants as recently reported by the IEA…”
Section: Resultsmentioning
confidence: 99%
“…However, on an industrial scale, it is common practice to feed methanol reactors with syngas close to the stoichiometric condition (optimal SN is 2.05 as investigated by Løvik and co-workers) and excess of H 2 (2 < H 2 /CO < 3) with a variable amount of CO 2 (i.e., variable COR) according to the installed syngas generation technology. This means that the most common case in an industrial plant is represented by bio-syngas and petro-syngas feedstocks as reported in the literature case studies ,, and real methanol industrial plants’ data. , However, CO 2 /H 2 mixtures as feedstocks for methanol synthesis are under investigation, and they are becoming more and more appealing for their sustainability and environmental reasons , although carbon capture utilization and sequestration (CCUS) still represents a relevant cost factor in industrial plants as recently reported by the IEA…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the kinetics are slow due to limited transport/desorption of products from the active centers and thus the overall reaction yield is low [5]. The thermodynamics can be positively influenced by (Le Chatelier principle), and kinetic constraints can be lowered by the use of so-called sorption enhanced catalysis [4,[6][7][8]. The concept of sorption enhanced catalysis makes use of the fact that the reaction kinetics are controlled by the concentration of reactants and products at the reaction centres, which is modified by active removal of the product.…”
Section: Introductionmentioning
confidence: 99%
“…This method shifts a flow of seawater more acidic, causing the flow to release gaseous CO 2 that can then be collected. After collection, the CO 2 can be combined with hydrogen to produce a synthetic fuel [31][32][33][34], which can then be used in place of fossil fuels, completing the anthropogenic carbon cycle, or stored, removing the carbon from the Earth's carbon cycle. One such device that incorporates this process is the renewable energy powered methonal-producing island [32] (referred to as a methanol island from now on), shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…More explicitly, the device operates by extracting the atmospheric CO 2 dissolved in the seawater with an electrochemical extraction module and combines it with hydrogen gas, sourced from desalinated water that is separated into hydrogen and oxygen gas. The carbon dioxide and hydrogen gasses react in a reactor, producing methanol [33]. In our study, we are interested in determining the optimal locations to put such a device in the Mediterranean Sea.…”
Section: Introductionmentioning
confidence: 99%